Changes in Meaning in the Latest News on Liputan6.com - Fadila, Nazhifa; Charlina, Charlina; Sinaga, Mangatur (CV. Rayyan Dwi Bharata, 2024)
When writing news, changes in meaning influence the variety of language used by journalists, namely the presence of new vocabulary and adapting words to the context. The aim of this research is to describe the types and factors that influence changes in meaning in the latest news on Liputan6.com. The research method used is descriptive qualitative. The results of the research found 5 types of meaning changes, the dominant of which was widespread meaning change and 8 dominant factors of meaning change were term development. The five changes in meaning, namely (1) broadened meaning, (2) narrowed meaning, (3) refined meaning (eufemia), (4) coarsened meaning (dysphemia), and (5) total change meaning. Factors that influence changes in meaning are (1) developments in science and technology, (2) social and cultural developments, (3) differences in fields of use, (4) the existence of associations, (5) exchange of sensory responses, (6) differences in responses , (7) grammatical processes, and (8) term development. (200-250)